Prevalence of Vitamin D Insufficiency/Deficiency and Their Role in Atopic Dermatitis Development and Course in Children - Tatiana S. Kashinskaya; Natalia V. Shakhova; Yrij F. Lobanov; Elena M. Kamaltynova ("Paediatrician" Publishers LLC, 2022)
Various conclusive evidence on the role of vitamin D in the pathogenesis of atopic dermatitis (AD) has been obtained in recent decades. Many studies have shown that patients with AD have low concentration of 25(OH)D in blood associated with high concentration of allergen specific IgE (according to several reports). The analysis of low 25(OH)D concentration prevalence, association of vitamin D deficiency with AD severity and sensitization to allergens, and association of vitamin D disorders with risk of AD development is presented.